Cardiovascular Magnetic Resonance Myocardial Feature Tracking: Concepts and Clinical Applications. (April 2016) - Schuster, Andreas; Hor, Kan N.; Kowallick, Johannes T.; Beerbaum, Philipp; Kutty, Shelby
Abstract : Heart failure–induced cardiovascular morbidity and mortality constitute a major health problem worldwide and result from diverse pathogeneses, including coronary artery disease, nonischemic cardiomyopathies, and arrhythmias. Assessment of cardiovascular performance is important for early diagnosis and accurate management of patients at risk of heart failure. During the past decade, cardiovascular magnetic resonance myocardial feature tracking has emerged as a useful tool for the quantitative evaluation of cardiovascular function. The method allows quantification of biatrial and biventricular mechanics from measures of deformation: strain, torsion, and dyssynchrony. The purpose of this article is to review the basic principles, clinical applications, accuracy, and reproducibility of cardiovascular magnetic resonance myocardial feature tracking, highlighting the prognostic implications. It will also provide an outlook on how this field might evolve in the future.